A Comparative Study of Using Analytic and Holistic Methods of Scoring in Measuring Speaking Skill Among Iranian Second-grade University EFL Students - Behrouz Ahmadi; Ehsan Namaziandost; Parisa Etemadfar (Journal of English Language Studies, 2020)
Evaluating the speaking skill is in fact complicated and rigid. Two methods of assessing the speaking completion are analytic and holistic scoring. The methods of investigating the oral skill were investigated deeply. Spoken skills of English belonging 70 individuals, those were Iranian second-grade university EFL students, were evaluated by speaking addressee and examiner. The speaking addressee performs the holistic scoring though the examiner directed the analytic scoring. Context and construction, vocabulary, grammar and pronunciation are the classes of analytic scoring. The analytic mean of four scales was 3.396, although the mean of holistic scoring was 3.628. The results showed a statistically considerable diversity between analytic and holistic methods of evaluation considering that p-value was estimated at 0.002 (P < 0.05). Therefore, it is recommended that employing these two scoring techniques in the procedure of evaluation may be considered proper seeing that one augment the other and lead to more inclusive evaluation.